Consumer Loyalty: Service Quality and Emotional Satisfaction - Eka Pranajaya; Dwinanto Priyo Susetyo; Deri Firmansyah (Economics and Digital Business Review, 2023)
Feelings and emotions can play the role of markers, mediators and moderators of the response of consumer behavior to products and services received. Feelings do not have the nature of a liar not even a liar, so provide pleasure, joy and happy feelings of customers through relationships, products and services and attributes to increase their loyalty. This study empirically examines the relationship between service quality (ServQUAL), emotional satisfaction (ES) and customer loyalty (CL). The mediated effect of ES was tested and analyzed. ServQUAL and ES as cognitive and affective aspects were considered as CL frameworks, by deploying instruments to 165 selected samples, respondents responses were analyzed using a simple path with the help of the EViews v10 program. Research findings, from structural analysis I, it is known that ServQUAL has a significant positive effect on customer ES. The results of structural analysis II, found ES to have a significant positive effect on CL. Sobel test results that ServQUAL has a significant positive influence on CL both directly and indirectly through ES. The role of ES was shown to have a mediating effect on the relationship and the influence of ServQUAL on CL. The positive and negative ES aspects of this study were not verified further, it could be the direction of further research.